1999
DOI: 10.1271/bbb.63.951
|View full text |Cite
|
Sign up to set email alerts
|

16-O-Demethyl Fusicoccin J and Its 3-Epimer fromFusicoccum amygdali, and Their Seed Germination-stimulating Activity in the Presence of Abscisic Acid

Abstract: Our search for new metabolites biosynthetically related to fusicoccin with potent plant growth-stimulating actiyity from the culture Mtrate of fusicoccum amJtgtinli F6 resulted in the isolation of a new deriyatiye of fusicoccin J, as well as fusicoccin J and 16-O-demethyl 3-epifusicoccifi J. Its structure was analyzed by 600 MHz NMR spectrometry and identified as 16-O-demethyl fusicoccin J. The biosynthetic relationships among 16-O-demethyl fusicoccin J and its 3-epimer, and f-sicoccin J are discussed in conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Its relative stereochemistry has been elucidated, but its absolute conˆguration has not previously been determined. In our current eŠort to isolate new fusicoccins from the fungus, it was found that P. amygdali F6a 4) (the Italian strain) produced fusicoccin J together with new 16-O-demethylfusicoccin J, and that P. amygdali Niigata 2 5) (the Japanese strain) produced 3?-deacetylfusicoccin A together with new 3-epifusicoccins. 6) We also isolated (+)-menthol (1) as a novel fungal metabolite from the cultureˆltrate of the Niigata 2 strain, and its related metabolites, (+)-(1R,3S,4R,6S )-6-hydroxymenthol (3) as a new compound and (+)-(1S,3S,4R)-7-hydroxymenthol (2), and known 4 from a cultureˆltrate of the F6a strain (Fig.…”
Section: Abstract: (+)-Menthol; (+)-7-hydroxymenthol; (+)-(6s )-Hydrmentioning
confidence: 90%
See 2 more Smart Citations
“…Its relative stereochemistry has been elucidated, but its absolute conˆguration has not previously been determined. In our current eŠort to isolate new fusicoccins from the fungus, it was found that P. amygdali F6a 4) (the Italian strain) produced fusicoccin J together with new 16-O-demethylfusicoccin J, and that P. amygdali Niigata 2 5) (the Japanese strain) produced 3?-deacetylfusicoccin A together with new 3-epifusicoccins. 6) We also isolated (+)-menthol (1) as a novel fungal metabolite from the cultureˆltrate of the Niigata 2 strain, and its related metabolites, (+)-(1R,3S,4R,6S )-6-hydroxymenthol (3) as a new compound and (+)-(1S,3S,4R)-7-hydroxymenthol (2), and known 4 from a cultureˆltrate of the F6a strain (Fig.…”
Section: Abstract: (+)-Menthol; (+)-7-hydroxymenthol; (+)-(6s )-Hydrmentioning
confidence: 90%
“…Phomopsis ( Fusicoccum) amygdali F6a 4) was reciprocally shake-cultured for 4 days at 259 C in 500-ml Sakaguchi ‰asks, each containing 100 ml of an 8z sugar-0.5z peptone-1.0z corn steep liquor-0.5z NaCl medium. The cultureˆltrate (ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15) However, significant differences between them in the ½ D and chemical shift values (Á þ1:4-À1:9 ppm) of the 13 C-NMR signals (C-1, 5, 16, and 17 in Table 1) were apparent. In addition, careful irradiation at the 17-H signal of substance A did not produce any DIF-NOE signals of 16-H. 14) These observations suggested that substance A was the 3-epimer of O-demethylcotylenol. The stereochemistry of substance A was elucidated by DIF-NOE spectrometry, using a 600 MHz NMR spectrometer: DIF-NOEs in substance A were observed not only between 17-H and 9-H/4 -H ( 1.66), and 18-H and 9-H, but also between 6-H and 8-H/5 -H ( 1.90), and 16-H ( 3.40) and 5 -H/4 -H ( 1.79) (Fig.…”
Section: Methodsmentioning
confidence: 85%
“…Fraction 3 was rechromatographed by a similar method, using a 19:1 mixture of CHCl 3 /EtOH and then a 31:1 mixture of EtOAc/EtOH, to give fine colorless crystals (18 mg). Substances B and C were detected together with 16-O-demethyl-FC J 14) in fraction 4 (7:1 CHCl 3 / EtOH). These were separated by a similar method, using EtOAc/EtOH mixtures, to give 5 fractions.…”
Section: Methodsmentioning
confidence: 99%